The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.22610/jebs.v6i4.494
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Bank Efficiency in South Africa Using the Standard and Alternative Approaches to Data Envelopment Analysis (DEA)

Abstract: The paper investigates the efficiency of the major banks of South Africa using the standard and alternative approaches to Data Envelopment Analysis (DEA). The standard DEA approach measures efficiency utilising linear averages of outputs and inputs while the alternative DEA approach utilises nonlinear averages. Individual bank efficiency scores are estimated over the period 2006 to 2012, a period that allows analysis of the efficiency of the banks during the global financial crisis of 2008 to 2009. Under both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
(48 reference statements)
2
17
0
Order By: Relevance
“…It is the only country in the world that has mandated the integrated reporting for the public listed companies ( Financial services sector in general and banking in particular, is an important sector because what happened in the global financial crisis in 2008-2009 emanated from this sector as a result of too much risk being taken within very little transparency and reporting climate (Cerasi & Oliviero, 2015). Although South African banking sector was largely insulated from the global financial crisis (Erasmus & Makina, 2014), the sector remains an important player in the economy.…”
Section: Studies On Integrated Reportingmentioning
confidence: 99%
“…It is the only country in the world that has mandated the integrated reporting for the public listed companies ( Financial services sector in general and banking in particular, is an important sector because what happened in the global financial crisis in 2008-2009 emanated from this sector as a result of too much risk being taken within very little transparency and reporting climate (Cerasi & Oliviero, 2015). Although South African banking sector was largely insulated from the global financial crisis (Erasmus & Makina, 2014), the sector remains an important player in the economy.…”
Section: Studies On Integrated Reportingmentioning
confidence: 99%
“…Akomea-Frimpong (2017) finds that foreign banks are not necessarily more efficient than their domestic rivals. Erasmus and Makina (2014) showed that the global financial crisis did not affect the efficiency of the majority of the banks. Since the banks were efficient prior the crisis, it could be argued that their efficiency was one of the contributory factors for their resilience during the global financial crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Maimbo (2002) found that a lack of enforcement and supervisory forbearance undermine the key role played by those institutions and increase the risk of bank failure. In South Africa, the banking supervisory system protected banks against market change and negative impact of the crisis (Van der Westhuisen, 2013; Erasmus and Makina, 2014). Banks supervisory department of the South Africa Reserve Bank also defines bank legislation and international standards to be followed by all banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies conducted around bank performances in South Africa, focused on the period around the financial crisis that occurred in 2007(Van Heerden and Heymans, 2013). However, the study conducted by Erasmus and Makina (2014) showed that the effect of financial crisis on the South African banking system was minimal because of the sound supervisory system (Van der Westhuisen, 2013) and the low exposure to foreign currency debt (Kumbirai and Webb, 2010). This implies that considering the financial crisis event on research related to South African bank performance is not significant.…”
Section: Literature Reviewmentioning
confidence: 99%